A Psycholinguistic Analysis to the film Midnight in Paris with Reference to Nostalgia - Lanja Abdul Razzaq Dabbagh (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Decades ago, nostalgia was viewed as a disease; now it is considered to be an essential psychological resource which have a great value to human life. True, it is a topic that most common, ordinary, laypeople are acquainted with, but it is a topic that researchers, scientists, writers, and academics have a huge interest in. The the aim of the current paper is to discuss the topic of nostalgia and how it is considered to be a phenomena where people involve in deeply, they experience an improvement in positive psychological states such as positive mood, feelings of social connectedness, self-esteem, self-continuity, and insights of meaning in life. The paper answers the question of why and how people differ in their tendency to be nostalgic. This is done through language analysis of the film Midnight in Paris. This film has a nostalgic theme and it has been analyzed likewise. The purpose, here,is to analyze the language used in the film which emphasizes on the topic of nostalgia. One of the main conclusions arrived at, is the fact that language choices are strongly affected by the psychological condition of the speaker in expressing nostalgic feelings associated with imagination.